2021
DOI: 10.1016/j.jbc.2021.101257
|View full text |Cite
|
Sign up to set email alerts
|

The eIF2 kinase GCN2 directs keratinocyte collective cell migration during wound healing via coordination of reactive oxygen species and amino acids

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Furthermore, SCD1 deletion significantly increases energy expenditure under cold stress to compensate for the heat loss due to impaired barrier function ( 53 ). Another concept worth consideration is compromised skin function, as observed during wound healing in keratinocytes lacking GCN2 ( 58 ). In this work, genetic deletion or pharmacological inhibition of GCN2 in keratinocytes delayed collective cell migration and wound closure, with the major effect involving a failure to maintain intracellular free cysteine and a loss of reactive oxygen species coordination at the wound site.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, SCD1 deletion significantly increases energy expenditure under cold stress to compensate for the heat loss due to impaired barrier function ( 53 ). Another concept worth consideration is compromised skin function, as observed during wound healing in keratinocytes lacking GCN2 ( 58 ). In this work, genetic deletion or pharmacological inhibition of GCN2 in keratinocytes delayed collective cell migration and wound closure, with the major effect involving a failure to maintain intracellular free cysteine and a loss of reactive oxygen species coordination at the wound site.…”
Section: Discussionmentioning
confidence: 99%
“…Arriazu et al demonstrated that amino acid deprivation decreases intracellular ROS levels in hepatic stellate cells in vitro, with this effect shown to be dependent on GCN2 but not on downstream eIF-2α [91]. Deletion or pharmacological inhibition of GCN2 significantly delays collective cell migration and wound closure by impairing the maintenance of intracellular free amino acids, particularly cysteine, as well as disrupting Ras-related C3 botulinum toxin substrate 1 (RAC1)-GTP-driven ROS generation, lamellipodia formation, and focal adhesion dynamics in human epidermal keratinocytes during wound healing [92]. Furthermore, GCN2 and its downstream signaling pathway play important roles in protection against oxidative injuries induced by an amino acid imbalanced diet [93].…”
Section: Gcn2 and The Oxidative Stress Responsementioning
confidence: 99%
“…Loss of GCN2 and the accompanying lowered amino acids would render cells more vulnerable to UV stress ( 25 , 53 ). GCN2 and its maintenance of amino acids was also reported to be central for coordination of ROS in keratinocytes subjected to wounding ( 28 ). These results support the model that diminished levels of amino acids and charged tRNA is central for activation of GCN2 in response to UV stress.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were grown in Dulbecco's Modified Eagle Medium media (DMEM, Corning, #10-013-CV) supplemented with 10% (v/v) fetal bovine serum (Corning, #35-010-CV), 100 units/ml penicillin and 100 μg/ml streptomycin (Cytiva, #SV30010). An immortalized human keratinocyte cell line, NTERT, which has been shown to have normal differentiation properties ( 24–29 ), was maintained and passaged in low calcium EpiLife Complete media (Gibco, #MEPI500CA) supplemented with human keratinocyte growth supplement (HKGS; Themo Fisher Scientificc, #S0015) and 1000 U Penicillin-Streptomycin (PS) (Gibco Laboratories, #15140122) as previously described ( 28 ). Mouse embryonic fibroblast (MEF) cells were cultured in DMEM supplemented with 10% FBS as previously described ( 30 ).…”
Section: Methodsmentioning
confidence: 99%